2006
DOI: 10.1111/j.1467-7652.2006.00181.x
|View full text |Cite
|
Sign up to set email alerts
|

Abundant transcripts of malting barley identified by serial analysis of gene expression (SAGE)

Abstract: SummarySerial analysis of gene expression (SAGE) was applied to the major cereal crop barley ( Hordeum vulgare ) to characterize the transcriptional profile of grain during the malting process. Seven SAGE libraries were generated from seed at different time points during malting, in addition to one library from dry mature seed. A total of 155 206 LongSAGE tags, representing 41 909 unique sequences, was generated. This study reports an in-depth analysis of the most abundant transcripts from each of eight specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
26
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 35 publications
4
26
0
1
Order By: Relevance
“…Up-regulation of genes involved in metabolism of carbohydrates, nucleotides, amino acids, and proteins during steeping indicates that a reactivation of metabolism was occurring. Twentyfour hours following steeping (day 1), extensive reprogramming of gene expression occurred, similar to what others have previously reported (Watson and Henry 2005;White et al 2006). Every functional category included in the analysis increased in the number of induced genes during the malting stages.…”
Section: Transcript Prowles Of Germinating Barley Seedssupporting
confidence: 83%
See 2 more Smart Citations
“…Up-regulation of genes involved in metabolism of carbohydrates, nucleotides, amino acids, and proteins during steeping indicates that a reactivation of metabolism was occurring. Twentyfour hours following steeping (day 1), extensive reprogramming of gene expression occurred, similar to what others have previously reported (Watson and Henry 2005;White et al 2006). Every functional category included in the analysis increased in the number of induced genes during the malting stages.…”
Section: Transcript Prowles Of Germinating Barley Seedssupporting
confidence: 83%
“…Genes involved in stress and defense response made up a major portion of diVerentially expressed transcripts in all four malting stages studied. Previous studies of germinating barley seeds have reported similar Wndings (Potokina et al 2002;Watson and Henry 2005;White et al 2006). This is not surprising since malting is not performed under aseptic conditions and barley seeds contain an inherent microbial Xora consisting of fungi, bacteria, and yeasts (Flannigan 2003).…”
Section: Transcript Prowles Of Germinating Barley Seedssupporting
confidence: 62%
See 1 more Smart Citation
“…None of the 56 differentially expressed genes corresponded to proteins associated with mobilization of the major seed starch and storage protein reserves or cell wall carbohydrates during malting Potokina et al 2004;White et al 2006).…”
Section: Malting Quality Footprintsmentioning
confidence: 99%
“…Large-scale gene expression technologies such as cDNA-and oligonucleotide-based arrays, and serial analysis of gene expression (SAGE) have proved to be useful to conduct transcript profiling during germination and malting (Lapitan et al 2009;Potokina et al 2002Potokina et al , 2004Watson and Henry 2005;White et al 2006), and to identify candidate genes for malting quality (Lapitan et al 2009;Potokina et al 2004Potokina et al , 2006.…”
Section: Introductionmentioning
confidence: 99%